Hyper-Immune Bovine Milk as an Immunological and Nutritional Supplement for COVID-19 - Nili, Hassan; Bouzari, Majid; Attaran, Hamid Reza; Ghalegolab, Nader; Rabani, Mohammad; Mahmoudian, Ahmad (Frontiers in Nutrition, 2022)
Many different strategies have been used to fight against the COVID-19 pandemic as a therapeutics or prophylaxis approaches. However, not enough attention has been paid to general and specific immune factors and nutritional components found in dairy products of hyper-immunized farm animals, which can help COVID-19 patients in one way or another. Hyper-immune bovine colostrum (HBC) has been used against many different respiratory and gastrointestinal tracts infections during past decades. An isolated dairy farm was established, and nine mixed Holstein X Semental dairy cattle in their 6-7 months of gestation period were chosen for hyper-immunization with inactivated SARS Cov-2.For this, six cows were inoculated with 2 ml of 109.4/ml (TCID50) of the virus. As a control group, three cows were inoculated with the carrier without virus. Specific IgG level against the SARS-CoV-2 was measured before and after immunization in the sera, and in the colostrum and milk following parturition in hyper-immunized cows. Neutralizing antibodies in colostrum was measured by a quantitative ELISA. The safety of the product was determined in 40 healthy volunteers in the phase 1 clinical trial (https://www.irct.ir/trial/51259). No adverse effects were observed in the experimental cows. A very high level of IgG was observed in the first colostrum that sharply decreased in the following seven days in the milk. The titer of specific neutralizing antibody in the colostrums was 69 times higher than the sera. No adverse effects and clinical complications were reported by the authorized ethics committee, and an official certificate on the safety of the product was issued. Beside other strategies, this approach could be used for large-scale and low-cost production of immune components to be used as a nutritional supplement to confront current SARS-CoV-2 and future pandemics.